Japan fund for poverty reduction annual report 2020 (Progress reports of the Japan fund for poverty reduction., 2021)
The JFPR is a partnership between the Government of Japan and ADB. It provides grants and technical assistance to reduce poverty in ADB developing member countries. It also promotes long term social and economic development in the countries, to add substantive value and development impact to ADB assistance.